Formulation and Evaluation of Orally Disintigrating Tablet of Lamotrigine - Sharma, Vinay; Singh, Surya Pratap; Nama, Nitin; Khinchi, M. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
The objective of the present study was to develop orally disintegrating tablet of Lamotrigine, for treatment of epilepsy. It is also used in simple and complex partial seizures and secondary generalized tonic-clonic seizures. The results obtained revealed that solubility of the drug markably increased with both the polymers but as PVP K-30 itself act as a binder in tablet formulation, it increases the disintegration time so it was not suitable for the formulation of ODT. So for the preparation of solid dispersion β-CD was used in 1:1drug carrier ratio as revealed by phase solubility studies .The prepared tablets were evaluated for organoleptic characteristics like color, odor, taste and physical characteristics like diameter, thickness, hardness, friability, weight variation, disintegration time, and dissolution studies. Based on these parameters, concentration of SSG & crospovidone were selected for further studies. Results revealed that the concentration of SSG and Crosspovidone significantly affected the dependent variables (disintegration time, wetting time and %friability).Optimum formulation was suggested by the software.